2021
DOI: 10.1002/cre2.488
|View full text |Cite
|
Sign up to set email alerts
|

Influence of professional dental hygiene on oral and general health of retirement home residents: A comparative study

Abstract: Objectives: The oral status of nursing home residents is poor. This could compromise general health. The controlled study investigated the influence of quarterly professional dental hygiene interventions on oral and general health of elderly.Material and Methods: 152 participants (mean age 84 years) of two residents' homes were examined. Parameters of general health, a questionnaire for caregivers, and oral parameters were evaluated at baseline and after 1 year. All caregivers were given one lesson on oral hyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…After the removal of duplicates and other exclusion criteria, 492 studies were screened, and of these, 128 were shortlisted for inclusion based on the screening of their titles and abstracts. The full text of shortlisted studies was assessed for eligibility, and finally, 74 studies 4 , 10 , 11 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the removal of duplicates and other exclusion criteria, 492 studies were screened, and of these, 128 were shortlisted for inclusion based on the screening of their titles and abstracts. The full text of shortlisted studies was assessed for eligibility, and finally, 74 studies 4 , 10 , 11 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , …”
Section: Resultsmentioning
confidence: 99%
“…An overwhelming, 19 studies 12 , 20 , 21 , 25 , 29 , 30 , 31 , 33 , 39 , 41 , 63 , 66 , 73 , 74 , 75 , 76 , 79 , 81 , 84 assessed acrylic dentures, and only a single study 52 investigated metallic dentures, whereas another 43 investigated both acrylic and metallic dentures; the remaining 53 studies 4 , 9 , 10 , 14 , 15 , 16 , 17 , 18 , 21 , 22 , 23 , 25 , 26 , 27 , 31 , 33 , 34 , 35 , 36 , 37 , 39 , 41 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 63 , 64 , 66 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, a German study by Thederan and colleagues [11] that involved an analysis of the prevalence of the visual impairment, as well as its management, showed that many of these conditions were not treated correctly, and improvement was requested in terms of ophthalmological assistance as well as the personnel who took care of the patients, underlining the fact that there are still health shortages. Furthermore, a comparative study on the influence of occupational dental hygiene on the oral and general health of nursing home residents in September 2021 in the USA (152 participants in two nursing homes) to evaluate the influence of a quarterly treatment of occupational dental hygiene on general and oral health concluded that daily oral hygiene procedures are necessary for the oral health of resident patients in LTCFs [12]. This study effectively underlined the need for frequent interventions to optimize the health policy framework necessary to allow caregivers more time for oral hygiene and to establish the accessibility of frequent professional healthcare for the inhabitants of the homes of residents; therefore, there is a need for clear guidelines in the field of oral hygiene to support caregivers' adequate healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…This study effectively underlined the need for frequent interventions to optimize the health policy framework necessary to allow caregivers more time for oral hygiene and to establish the accessibility of frequent professional healthcare for the inhabitants of the homes of residents; therefore, there is a need for clear guidelines in the field of oral hygiene to support caregivers' adequate healthcare. This study further showed that the oral health of the elderly revealed a poor situation in terms of dental status, periodontal situation, and cleanliness of the prosthesis, tongue, and oral cavity [12][13][14][15][16][17][18][19][20][21]. Impaired oral health is influenced by multiple general health problems, such as dementia, frailty, psychological disorders, malnutrition, and multiple-drug secondary therapy [10].…”
Section: Discussionmentioning
confidence: 99%